Acetone Sensing Properties and Mechanism of Rh-Loaded WO3 Nanosheets - Qiu, Zhilei; Hua, Zhongqiu; Li, Yan; Wang, Mengjun; Huang, Dan; Tian, Chen; Zhang, Chensheng; Tian, Xuemin; Li, Erping (Frontiers in Chemistry, 2018)
In this paper, WO3 nanosheets were prepared by an acidification method and Rh catalyst was loaded on the surface of nanosheets through a wet impregnation process. The effects of Rh modification on structures and morphologies of WO3 nanosheets were investigated. WO3 gas sensors fabricated from the nanosheets were prepared and the sensing properties of acetone were investigated. Sensitization mechanis m on the sensing performance were analyzed based on the oxygen adsorption and TPR results. It was found that Rh-loading had no influence on the morphology of WO3 nanosheets, however, the sensor resistance and sensor response were greatly promoted. The basic sensitizat ion mechanis m could be caused by the electronic interaction between oxidized Rh and WO3 surface.